2010
DOI: 10.1111/j.1530-0277.2010.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Large Esophageal Varices by Fibroscan: Strong Influence of the Cirrhosis Etiology

Abstract: Etiology of cirrhosis has strong impact on LS cutoff for diagnosis of LOV. Studies should be performed with homogenous cirrhosis etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
(80 reference statements)
3
52
1
Order By: Relevance
“…The sensitivity of elastography for the presence of EV has been high in the majority of the studies we have reviewed (76-95%) but their corresponding specificity (43-78%) was significantly lower than the value we obtained [9,[21][22][23][24][25][26]. One explanation for this discordance may come from the fact that the reviewed studies were conducted on a population with a heterogenous ethiology of cirrhosis.…”
Section: Disscusionscontrasting
confidence: 46%
“…The sensitivity of elastography for the presence of EV has been high in the majority of the studies we have reviewed (76-95%) but their corresponding specificity (43-78%) was significantly lower than the value we obtained [9,[21][22][23][24][25][26]. One explanation for this discordance may come from the fact that the reviewed studies were conducted on a population with a heterogenous ethiology of cirrhosis.…”
Section: Disscusionscontrasting
confidence: 46%
“…A further two articles, by Rosenberg et al 121 and Melin et al, 122 were not identified by the electronic searches because they were not appropriately indexed in the electronic databases; they were supplied by the relevant manufacturers together with an unpublished paper by Parkes et al 57 One hundred and ninety-eight citations were excluded at the full-text stage, leaving 17 articles that were included in the review (Figure 4). These 17 articles related to 14 studies: one study of the ELF test, 57,121 four studies of FibroTest, 13,[123][124][125][126] eight studies of FibroScan 97,117,118,122,[127][128][129][130][131] and one study which used both FibroTest and FibroScan. 132 No studies of FibroMAX were identified.…”
Section: Quantity and Quality Of Research Availablementioning
confidence: 99%
“…A further three studies 97,129,130 evaluated the diagnostic test accuracy of FibroScan in patients with liver disease of mixed aetiology, including ALD. Bureau et al 129 studied the ability of FibroScan to predict significant PHt in patients undergoing transjugular liver biopsy for clinical reasons.…”
Section: Fibroscanmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, for a cut-off value of 50.7 kPa, LS had 82.7% PPV and 53.6% NPV (AUROC=0.730) for predicting esophageal bleeding. Published studies [60,61] showed that cut-off values for predicting the presence of large EV are significantly higher in patients with alcoholic as compared with those with viral etiology of chronic liver disease. A meta-analysis which included 18 studies, with more than 3,500 patients [62], showed that TE had 0.90 summary senisitivity with 0.79 summary specificity (AUROC=0.93) for detecting the presence of clinically significant portal hypertension (HVPG≥10 mmHg), 0.87 summary sensitivity with 0.53 summary specificity (AUROC=0.84) for predicting the presence of EV and 0.86 summary sensitivity and 0.59 summary specificity (AUROC=0.78) for detecting large EV.…”
Section: Te For Predicting Liver Cirrhosis Complicationsmentioning
confidence: 99%